Experience Effects in Auditing: The Role of Task-Specific Knowledge - Bonner, Sarah E. (The Accounting Review, 1990)
[Previous studies concerning experience effects in audit judgments have produced mixed results, possibly because they did not consider the knowledge necessary to complete the task and when it would normally be acquired. Further, many studies did not view the global judgment process as consisting of several components, e.g., cue selection. Task-specific knowledge may aid the performance of experienced auditors more in some components than in others. Not considering task-specific knowledge or viewing the judgment process as being comprised of components may have led to certain problems in generalizing the results of these studies to other auditing tasks. Those problems are addressed in the design of this study, which examines experience effects, specifically the role of task-specific knowledge, in the cue selection and cue weighting components of two audit tasks, analytical risk assessment and control risk assessment. Results indicate that task-specific knowledge aided the performance of experienced auditors in both the cue selection and cue weighting components only in analytical risk assessment.]